Incremental Prognostic Impact of Peripheral Microvascular Endothelial Dysfunction on the Development of Ischemic Stroke. Issue 9 (5th May 2020) - Toya, Takumi; Sara, Jaskanwal D.; Ahmad, Ali; Nardi, Valentina; Taher, Riad; Lerman, Lilach O.; Lerman, Amir
Abstract : Background: Peripheral microvascular endothelial dysfunction (PMED) has been linked to an increased risk of cardiovascular events, but there is a lack of information characterizing the predictive value of PMED for future risk of ischemic stroke (IS). Methods and Results: This retrospective observational cohort study enrolled 637 patients who underwent non‐invasive microvascular endothelial function assessment using reactive hyperemia peripheral arterial tonometry. Reactive hyperemia peripheral arterial tonometry index ≤2 was defined as PMED. Of 280 patients with PMED, 12 (4.3%) patients developed IS, compared with only 4 (1.1%) of 357 patients without PMED during a median follow‐up of 5.3 years. Patients with PMED had lower IS‐free survival compared with patients without PMED (log‐rank P =0.03). Cox proportional hazard ratio (HR) analyses showed that PMED predicted the incidence of IS, with a HR of 3.43, 95% CI, 1.10–10.63 ( P =0.03); adjusted HR of 3.70, 95% CI, 1.18–11.59 ( P =0.02) after adjusting for sex, smoking history, and atrial fibrillation; adjusted HR of 3.45, 95% CI, 1.11–10.72 ( P =0.03) after adjusting for CHA2 DS2 ‐VASc score; adjusted HR of 5.70, 95% CI, 1.40–23.29 ( P =0.02) after adjusting for revised Framingham Stroke Risk Score. Reactive hyperemia peripheral arterial tonometry index improved discrimination of risk for IS after adding reactive hyperemia peripheral arterial tonometry index to CHA2 DS2 ‐VASc score and revised Framingham Stroke Risk Score. Conclusions: PMED was associated with a >3‐fold increased risk of IS. These findings underscore the concept of the systemic nature of endothelial dysfunction, which could act as a potential marker to predict future risk of IS.